Nutrition strategies to optimise outcomes during critical illnes - Krishnasamy, Theevashini; A. Karim, Zeti Rahayu; Osman, Nora Julianna; Othman, Suraya; Rashid, Nor Faezan; Ahmad Nazlan, Mohd Fadhil; Abd Hamid, Muhammad Syamil; Zainal Abidin, Muhammad Fihmi (Faculty of Medicine, 2025)
The Department of General Surgery, Faculty of Medicine & Hospital Al- Sultan Abdullah (HASA), successfully organised the Talk on Nutrition 2025, focusing on the role of clinical nutrition in accelerating patient recovery and improving treatment outcomes.